Edukasi Aroma Terapi Lemon untuk Mengurangi Kecemasan pada Mahasisawa yang Akan Menghadapi Ujian Akhir Semester Program D3 Keperawatan Institut Batari Toja Bone - A. Artifasari; A. Sri Ulfi Nofriati (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
Anxiety in children and adolescents can lead to academic, sports and social performance problems. Anxiety also causes disturbances in the thought process, learning concentration, perception and can cause obstacles in the lives of those who are still studying which of course will affect their academic achievement. The mental health of students is a variable that needs attention as soon as possible. Because in addition to emotional factors, external factors can also be non-academic support/obstacles to the success of the learning process. Students of the Diploma Three Nursing study program at the Batari Toja Bone Institute, Academic Year 2024 experience different anxieties, where they will face final semester exam preparations, or practical exams. One of the complementary therapies used to overcome anxiety is the use of lemon aromatherapy by inhalation which can be done through a spray bottle or inhaled through tissue or gloves. The purpose and method of this community service activity is to conduct a Pre-test and Post-test then demonstrate and conduct lectures or counseling to students to reduce their anxiety when they are about to face the final semester exam using lemon aromatherapy. Based on the results of the counseling activities, it can be stated that before the counseling was given, 9 respondents (37%) experienced severe anxiety, 7 respondents (2.91%) experienced moderate anxiety, due to lack of knowledge. After being given counseling, it can be stated that 9 respondents (37%) experienced moderate anxiety, 6 respondents (25%) experienced mianxiety currently,